"I found it daunting": An exploration of educational needs and experiences of mental health student nurses working with children and adolescents with eating disorders. Issue 6 (3rd March 2020) - Farrington, Aoife; Huntley‐Moore, Sylvia; Donohue, Gráinne
Accessible summary: What is known about the subject?: A therapeutic relationship with a professional who displays an informed approach has a positive effect on outcomes for young people presenting with an eating disorder. There is a dearth of research available on the student mental health nurse experience of working with young people with an eating disorder both internationally and from the Republic of Ireland. Within this limited literature, nursing students were found to hold more negative perceptions towards this group than more experienced clinicians. The causes of eating disorders are complex, which make education and support to understand the individual with an eating disorder essential. Within the Republic of Ireland, child and adolescent mental health historically has received very little attention in the undergraduate mental health nursing curriculum. What does the study add to existing knowledge?: Findings from this study recommend that a set of guidelines are made available for students to feel more confident in their role. It is suggested that this resource would include the therapeutic skills to engage the young person with an eating disorder. A specialist clinical placement has been identified as the most appropriate time to consider the development of a study day or days to facilitate learning of the skills and therapeutic techniques to work with adolescents. Application of these skills would occur within the clinical learning environment under supervision and guidance of the clinical preceptor. What are the implications for practice?: Specialized training for student mental health nurses working with this group will enhance confidence and competence levels in forming therapeutic relationships, thereby improving outcomes for those attending the services. Better student experience may also enhance future nursing recruitment into this area. Students need additional support in managing these often complex and ambivalent presentations and their own fears or stigma around people with an eating disorder. This is recommended as taking the form of reflective practice during the placement. There is a need for nursing management to support nurses in their role as preceptor. This would involve protected time for preceptors to engage the student nurse in clinical education and reflective practice. Abstract: Introduction: There is limited attention given to child and adolescent mental health in the undergraduate mental health nursing curriculum within the Republic of Ireland. There is a dearth of research available on specifically the student mental health nurse experience both internationally and from the Republic of Ireland. Aim: To explore factors that impact on the experience of mental health student nurses working with adolescents who present with eating disorders. Method: This qualitative descriptive study was conducted through individual semi‐structured interviews with n = 4 mental health student nurses. Data were then subjected to a schematic content analysis. Results: The participants experienced developing therapeutic relationships with this group as a challenging process. They believed that the theoretical component of the undergraduate programme facilitated them in their understanding but did not prepare them to engage therapeutically with these adolescents. Discussion: Preceptors are identified as the main source of support but improvements to the clinical learning environment would enhance the learning experience. Implications for practice: Support for the role of the preceptor in the specialist clinical setting in the form of training and protected time to engage students in clinical education and reflection was suggested as a method to enhance the clinical learning environment.